2017
DOI: 10.1038/eye.2016.308
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes of external dacryocystorhinostomy and risk factors for functional failure: a 10-year experience

Abstract: The overall surgical outcomes of external DCR were favorable in this case series. Site of obstruction was an important risk factor for functional failure in cases with primary lacrimal drainage obstruction. A small lacrimal sac was also found to be a risk factor for functional failure in cases with primary NLDO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 25 publications
4
27
0
2
Order By: Relevance
“…Our findings support the assertion that DCR is a more suitable option for management of CCO or canalicular obstruction rather than canalicular trephination or canaliculoplasty, considering the possibility of combined lacrimal sac changes. In terms of success rate of external DCR, the functional success rate was higher in the primary NLDO group than in CCO or canalicular obstruction, in agreement with previous studies [ 5 13 14 ]. In cases of thick CCO, the status of the lacrimal sac affected the functional success rate, and this is a novel finding that has not been previously reported.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings support the assertion that DCR is a more suitable option for management of CCO or canalicular obstruction rather than canalicular trephination or canaliculoplasty, considering the possibility of combined lacrimal sac changes. In terms of success rate of external DCR, the functional success rate was higher in the primary NLDO group than in CCO or canalicular obstruction, in agreement with previous studies [ 5 13 14 ]. In cases of thick CCO, the status of the lacrimal sac affected the functional success rate, and this is a novel finding that has not been previously reported.…”
Section: Discussionsupporting
confidence: 91%
“…The purpose of this study was to classify the locational patterns of lacrimal drainage obstruction and the status of the lacrimal sac in CCO or canalicular obstruction cases based on intraoperative observation during external DCR surgery. Recently, we reported the surgical outcomes of 10 years of external DCR and the risk factors associated with functional failure [ 5 ]. Anatomical success was achieved in 98.8% of cases (760 / 769) and functional success in 81.9% (630 / 769).…”
mentioning
confidence: 99%
“…; Lee et al. ) and for the endonasal approach to 84%‐98% (Tsirbas & Wormald ; Tsirbas et al. ; Unlu et al.…”
Section: Discussionmentioning
confidence: 99%
“…11 We removed whole sac in long standing dacryocystitis to avoid failure and patient's agony of reoperations. Smaller fibrosed sacs are documented to have high failure risk 12 . Diverse aspects of causes of failed DCR have been reported in literature ranging from cicatricial ostium closure, scarring of common canaliculus, distal canalicular obstruction, granuloma formation and bone neogenesis 16 .…”
Section: Discussionmentioning
confidence: 99%
“…If these sacs are to be left in place they are source of recurrent infections and failed procedure due to insufficient marsupialization 11 . Lee et al has reported small sacs to have a high risk of failure 12 . Endolaser equipment for DCR is expensive, needs more expertise and is not available in our setup.…”
Section: Introductionmentioning
confidence: 99%